Peripherality and Integration: Industrial Growth and Decline in the Greek Regions - George Petrakos; Georgios Fotopoulos; Dimitrios Kallioras (European Regional Science Association (ERSA), 2006)
An empirical model has been deployed to account for regional industrial growth and performance in Greece's post EU-accession period. The results obtained suggest that the effect of European integration on manufacturing has been rather adverse across Greek regions. Regions that are more industrialised, whose structure was more similar to the European average and which have been more exposed to European competition are those that have been more adversely affected. In contrast, higher diversity, higher presence of capital intensive sectors and higher tertiarisation of the regional economies were found to be beneficial to regional industrial growth and performance.
Keywords: 330